Najnowsze tendencje zachodzące w przestrzeni społeczno-ekonomicznej z uwzględnieniem miast - Pięta-Kanurska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The development of the knowledge and technologies at the end of 20th and the beginning at the of 21st century caused many changes - also in the spatial organization of global economy. Greater significance is attached to the information and innovations in the economy. Moreover, the specific organisational developed into networks and metropolies are treated as their nodes. This situation implies many socioeconomic changes in the urban space. The article discusses the impact of chosen tendencies on the shaping of contemporary spatial structures including the role of big cities. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 111-123